SEDIMENTOLOGICAL AND GEOPHYSICAL OBSERVATIONS IN THE DELTA PLAIN OF SELINOUS RIVER, ANCIENT HELIKE, NORTHERN PELOPONNESUS GREECE - Koutsios, A.; Kontopoulos, N.; Kalisperi, D.; Soupios, P.; Avramidis, P. (Bulletin of the Geological Society of Greece, 2010)
Fine and coarse grained lithofacies and depositional environments were distinguished in Selinous River delta plain, from sediment cores using an Eijkelkamp percussion corer with barrel windows. The sedimentary sequence of deltaic plain deposits of Selinous River mostly consists of fine lithofacies interbedded occasionally with conglomerate facies. Fine grained lithofacies based on sediment types, structure, color, as well as contact depths and bed characteristics were interpreted as floodplain, crevasse splay, back swamp / fresh water swamp, permanent shallow fresh water lake and ephemeral fresh water lake facies. The coarse grained lithofacies consists of pebble - conglomerates and were interpreted as paleochannels. The Time-Domain Electromagnetic technique, (TEM) was applied in order to define the spatial distribution of lenses of conglomerates, palaeochannels and fine grained sedimentary material to be recognised, at a depth up to 35m. Both the sedimentological and geophysical approaches, in combination with the available geological and geomorphological data of the area, can provide information about the evolution, existence and the geometry of paleochannels of the Selinous River flood plain, and the paleoenvironment of the area of the ancient Helike.